Estrogen Receptor Downregulates Expression of PD-1/PD-L1 and Infiltration of CD8+ T Cells by Inhibiting IL-17 Signaling Transduction in Breast Cancer - Shuai, Chong; Yang, Xinmei; Pan, Hongming; Han, Weidong (Frontiers in Oncology, 2020)
Background: The relationship between the interleukin 17 (IL-17) family of cytokines and breast cancer has been widely studied in recent years. Many studies have revealed increased levels of the cytokine IL-17A in estrogen receptor (ER)-negative or triple-negative breast cancer. Upregulation of IL-17A signaling is associated with increased expression of programmed cell death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) in breast cancer with low ER expression and may elevate the infiltration of CD8+ T cells in tumor tissue. This study aims to determine whether ER downregulates the expression of PD-1/PD-L1, reduces the infiltration of CD8+ T cells and affects the immune microenvironment by decreasing T-helper 17 (Th17) cell infiltration and inhibiting IL-17 signaling in breast cancer. Methods: Samples in The Cancer Genome Atlas Breast Cancer dataset were grouped by ER status and the PAM50 intrinsic subtype. The expression of IL-17 family cytokines and Th17 cell signature cytokines were compared between groups. IL-17 signaling pathway-related genes that were differentially expressed according to the ER level were identified. The PD-1 and PD-L1 levels were compared between breast cancer samples with different ER statuses and IL-17A/IL-17F expression levels. Correlation analyses of the expression of PD-1/PD-L1 and IL-17 signaling pathway-related genes were performed. The associations of the expression of IL-17 signaling pathway-related genes with the immune microenvironment were investigated. Results: High levels of ER decreased the expression of IL-17A, IL-17C and IL-17F but increased the expression of IL-17E (IL25), which acts as a suppressor of IL-17 signaling. The expression levels of Th17 cell signature cytokines were significantly increased in ER-negative breast cancer. The expression levels of genes encoding downstream products of IL-17A/IL-17F signaling were downregulated in breast cancer with high ER expression. Increased expression of PD-1/PD-L1 was associated with ER-negative status, IL-17A-positive status, IL-17F-positive status and upregulation of IL-17 signaling pathway-related genes in breast cancer. Enhanced IL-17 signal transduction was associated with the elevation of CD8+ T cell infiltration and variation of the immune microenvironment of breast cancer. Conclusion: High estrogen receptor levels decrease PD-1/PD-L1 expression and CD8+ T cell infiltration by suppressing Th17 cell infiltration and IL-17 signal transduction in breast cancer.